Chiral separation of pharmaceuticals by capillary electrophoresis - Huang, Xingye (2010)
Conventional capillary zone electrophoresis (CZE) methods, with simple buffer solute, natural or derivatized cyclodextrin and organic additive in BGE, have been developed for a group of ten standard chiral pharmaceutical compounds representing different physiochemical properties and pharmaceutical activities. In this study, factors affecting chiral separation in CZE, including BGE pH value, ionic strength, chiral selector type, selector concentration and organic additives, were optimized. A maximum of eight standard compounds were separated by three different standard methods which were developed. The electrophoretic behaviours of the standard compounds observed were in good agreement with the literature. Partial filling technique (PFT) was studied as a complementary approach to conventional CZE methods for enantioseparation of standard compounds. Partial filling time, selector type and concentration were investigated; a maximum of seven standard compounds were separated by optimized filling time and three different chiral selectors. However, for five of the separated pharmaceuticals, the chiral resolutions achieved were much lower than those obtained from conventional CZE methods. Key observations from the experiment were supported by previous research. For the first time, glycidol was evaluated as a covalently bonded coating material on CE capillary for enantioseparation.. Hyperbranched polyglycidol brushes were grown directly from Si/SiO2 surface via anionic ring-opening polymerization, using surface Si-OH groups as initiator. This grafting-form technique eliminated the need for initiator functionalized self-assembled monolayers on the surface, and the thickness and complexity of the hyperbranched polymer brushes could be well controlled in this process. Polyglycidol coating was established on the surface of glass slides and then adapted to CE capillary. Both fused silica capillary and etched capillary were used to examine the electrophoretic properties of polyglycidol coating. Chiral polyglycidol coating was compared with the standard CZE method developed and showed excellent chiral selectivity for standard compounds. Nine out of ten standard compounds were separated with poly-S-glycidol coated capillary, using simple buffer solute containing organic additive. Application of etched capillary further improved the enantioseparation resolution and peak efficiency for those standard compounds. Stability and coating regeneration ability were studied. Polyglycidol coating developed on CE capillary gradually lost its chiral selectivity after 50 30-min runs with acidic BGE. Coating regeneration on the remaining surface was difficult. The result indicated that glycidol isomer can be used as monomer for in situ polymerization in CE capillaries and the coating formed on the inner surface has potential chiral selectivity toward various pharmaceuticals, which is equal or better than traditional chiral CE.